Development of Performance Assessment Instruments for Measuring Drawing Skills in Vocational Students Competence in Mechanical Engineering Expertise - Ali Hasbi Ramadani; Ekohariadi Ekohariadi; Lilik Anifah; Yuli Sutoto Nugroho; Revi Safitri (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to develop a performance assessment instrument that can measure Drawing Skills in Machining Engineering Skills Competency Vocational School students, in addition to determining the feasibility and results of testing the performance assessment instrument. Method: This research is development research with a 4D Model, which consists of four stages, namely Defining, Designing, Developing, and Disseminating, and is limited to the development stage only. Results: The results of the research show that the vocational school students' drawing skills instrument for machining engineering skills competency was carried out by validating the contents of the instrument using the content validity ratio (CVR) method. Instrument trials were conducted at State Vocational School 2 Surabaya in the Machining Engineering skills program, totaling thirty-one students. Of the thirty instrument items developed, the test results referred to the CVR, total correlation, OMS, and IMS criteria; two items did not meet the requirements, so these items had to be revised or eliminated. Novelty: This research presents novelty by designing a particular Performance Assessment instrument to measure the drawing skills of vocational school students who have technical drawing competency, especially in the psychomotor aspect, so that it will make it easier for teachers to carry out assessments.